Keadilan Distributif dalam Zakat dan Pengentasan Kemiskinan Perspektif Asghar Ali Engginer - Wahyu Saputra (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
Asghar Ali Engineer is known as a Contemporary Islamic thinker. One of his thoughts also discusses Islamic economics, including the issue of Zakat. Asghar's thoughts on Zakat are based on a critique of the function of Zakat as a solution to the current poverty alleviation problem. In this research, the writer wants to describe the concept of distributive justice in Zakat. The author also wants to see how Asghar's process is formulating the idea. This research includes library research, which uses a qualitative approach. This study finds that distributive justice is the basis for building Islamic economics, and al-adl, al-ihsan, and al-qist are the keywords in distributive justice as universal values. Then Asghar's criticism of the problem of Zakat is related to the size of Zakat and how it is distributed. This thinking is based on his analysis of the current context, concluding that Asghar's process of understanding the text engages in a dialogue between the text and reality. Therefore, in this case, Asghar is a very contextual thinker.